Predicting disordered gambling across adolescence and young adulthood from polygenic contributions to Big 5 personality traits in a UK birth cohort. - Spychala, Kellyn M.; Gizer, Ian R.; Davis, Christal N.; Dash, Genevieve F.; Piasecki, Thomas M.; Slutske, Wendy S. (Addiction, 2022)
Background and Aims: Previous research has demonstrated phenotypical associations between disordered gambling (DG) and Big 5 personality traits, and a twin study suggested that shared genetic influences accounted for a substantial portion of this relation. The present study examined associations between DG and polygenic scores (PSs) for Big 5 traits to measure the shared genetic underpinnings of Big 5 personality traits and DG. Design: Zero-inflated negative binomial regression models estimated associations between Big 5 PSs and past-year and life-time assessments of DG in a longitudinally assessed population-based birth cohort. Setting: United Kingdom. Participants: A total of 4729 unrelated children of European ancestry from the Avon Longitudinal Study of Parents and Children (ALSPAC) with both phenotypical and genetic data. Measurements: Phenotypical outcomes included past-year assessment of DG using the problem gambling severity index (PGSI) and life-time assessment of DSM-IV pathological gambling symptoms (DPG) across the ages of 17, 20 and 24 years. Polygenic scores were derived for the Big 5 personality traits of agreeableness, extraversion, conscientiousness, openness and neuroticism using summary statistics from genome-wide association studies (GWAS). Findings: PSs for agreeableness [ß= - 0.25, standard error (SE) = 0.054, P = 3.031e-6, ΔR2 = 0.008] and neuroticism (ß=0.14, SE = 0.046, P = 0.0017, ΔR2 = 0.002) significantly predicted PGSI scores over and above included covariates (i.e. sex and first five ancestral principal components). PSs for agreeableness (ß= - 0.20, SE = 0.056, P = 0.00036, ΔR2 = 0.003) and neuroticism, when interactions with age were taken into account (ß = 0.29, SE = 0.090, P = 0.002, ΔR2 = 0.004), also predicted DPG scores. Conclusions: Polygenic contributions to low agreeableness and high neuroticism appear to predict two measures of disordered gambling (problem gambling severity index and life-time assessment of DSM-IV pathological gambling symptoms). Polygenic scores for neuroticism interact with age to suggest that the positive association becomes stronger from adolescence through young adulthood.